Primary Angiitis of the Central Nervous System: Description of the First Fifty‐Two Adults Enrolled in the French Cohort of Patients With Primary Vasculitis of the Central Nervous System. Issue 5 (May 2014) - de, Hubert; Zuber, Mathieu; Naggara, Olivier; Neau, Jean‐Philippe; Gray, Françoise; Bousser, Marie‐Germaine; Crassard, Isabelle; Touzé, Emmanuel; Couraud, Pierre‐Olivier; Kerschen, Philippe; Oppenheim, Catherine; Detante, Olivier; et al.
<x xml:space="preserve">Abstract</x> Objective To describe characteristics and outcomes of a multicenter cohort of patients diagnosed as having primary angiitis of the central nervous system (PACNS). Methods In 2010, we initiated a cohort study of adults diagnosed as having PACNS ≤15 years ago and with followup of >6 months (unless they died earlier of biopsy‐proven PACNS). Its first analysis was planned at 2 years. Multidisciplinary investigators verified that appropriate investigations were done and excluded patients with possible alternative diagnoses. We analyzed patient demographics and symptoms, laboratory, radiographic, and histologic findings, and treatments. Studied outcomes included treatment response(s), relapse, death, and disability. Results We included 52 patients (30 males; median age at diagnosis 43.5 years [range 18–79 years]) in whom PACNS was diagnosed between 1996 and 2012. Nineteen (61%) of 31 patients who had undergone brain biopsy had histologic vasculitis (biopsy‐proven PACNS), while the other 12 patients had normal or noncontributive biopsy samples. An additional 21 patients had signs suggestive of PACNS on conventional cerebral angiography. All but 1 patient received corticosteroids, and 44 patients received cyclophosphamide (CYC). After a median followup of 35 months (range 2–148 months) postdiagnosis (1 patient with biopsy‐proven PACNS died 2 months after diagnosis), 32 patients responded to treatment with improved modified Rankin scale scores, 4 patients (8%) did not respond, 14 patients (27%) had relapse of their disease at least once, and 3 patients (6%) died (1 patient after a relapse). Relapse was more common in patients with than in those without meningeal gadolinium enhancements on magnetic resonance imaging (MRI) (8 of 10 [80%] versus 6 of 32 [19%]; P = 0.001) and more common in patients with than in those without seizures at diagnosis (8 of 17 [47%] versus 6 of 35 [17%]; P = 0.04). Conclusion In this cohort of patients with PACNS, most patients received corticosteroids and CYC, and mortality was low. Patients with seizures at diagnosis or meningeal enhancements on MRI may be prone to relapse and require a different treatment strategy.